Solve for x
x=2007-2\sqrt{502}\approx 1962.189286995
x=2\sqrt{502}+2007\approx 2051.810713005
Graph
Share
Copied to clipboard
4028048-4014x+x^{2}=2007
Use the distributive property to multiply 2008-x by 2006-x and combine like terms.
4028048-4014x+x^{2}-2007=0
Subtract 2007 from both sides.
4026041-4014x+x^{2}=0
Subtract 2007 from 4028048 to get 4026041.
x^{2}-4014x+4026041=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-4014\right)±\sqrt{\left(-4014\right)^{2}-4\times 4026041}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, -4014 for b, and 4026041 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-4014\right)±\sqrt{16112196-4\times 4026041}}{2}
Square -4014.
x=\frac{-\left(-4014\right)±\sqrt{16112196-16104164}}{2}
Multiply -4 times 4026041.
x=\frac{-\left(-4014\right)±\sqrt{8032}}{2}
Add 16112196 to -16104164.
x=\frac{-\left(-4014\right)±4\sqrt{502}}{2}
Take the square root of 8032.
x=\frac{4014±4\sqrt{502}}{2}
The opposite of -4014 is 4014.
x=\frac{4\sqrt{502}+4014}{2}
Now solve the equation x=\frac{4014±4\sqrt{502}}{2} when ± is plus. Add 4014 to 4\sqrt{502}.
x=2\sqrt{502}+2007
Divide 4014+4\sqrt{502} by 2.
x=\frac{4014-4\sqrt{502}}{2}
Now solve the equation x=\frac{4014±4\sqrt{502}}{2} when ± is minus. Subtract 4\sqrt{502} from 4014.
x=2007-2\sqrt{502}
Divide 4014-4\sqrt{502} by 2.
x=2\sqrt{502}+2007 x=2007-2\sqrt{502}
The equation is now solved.
4028048-4014x+x^{2}=2007
Use the distributive property to multiply 2008-x by 2006-x and combine like terms.
-4014x+x^{2}=2007-4028048
Subtract 4028048 from both sides.
-4014x+x^{2}=-4026041
Subtract 4028048 from 2007 to get -4026041.
x^{2}-4014x=-4026041
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
x^{2}-4014x+\left(-2007\right)^{2}=-4026041+\left(-2007\right)^{2}
Divide -4014, the coefficient of the x term, by 2 to get -2007. Then add the square of -2007 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-4014x+4028049=-4026041+4028049
Square -2007.
x^{2}-4014x+4028049=2008
Add -4026041 to 4028049.
\left(x-2007\right)^{2}=2008
Factor x^{2}-4014x+4028049. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-2007\right)^{2}}=\sqrt{2008}
Take the square root of both sides of the equation.
x-2007=2\sqrt{502} x-2007=-2\sqrt{502}
Simplify.
x=2\sqrt{502}+2007 x=2007-2\sqrt{502}
Add 2007 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}